ABCA12 regulates insulin secretion from β‐cells. (18th February 2020) - Ursino, Gloria M; Fu, Ying; Cottle, Denny L; Mukhamedova, Nigora; Jones, Lynelle K; Low, Hann; Tham, Ming Shen; Gan, Wan Jun; Mellett, Natalie A; Das, Partha P; Weir, Jacquelyn M; Ditiatkovski, Michael; et al.
Abstract: Dysregulation of lipid homeostasis is intimately associated with defects in insulin secretion, a key feature of type 2 diabetes. Here, we explore the role of the putative lipid transporter ABCA12 in regulating insulin secretion from β‐cells. Mice with β‐cell‐specific deletion of Abca12 display impaired glucose‐stimulated insulin secretion and eventual islet inflammation and β‐cell death. ABCA12's action in the pancreas is independent of changes in the abundance of two other cholesterol transporters, ABCA1 and ABCG1, or of changes in cellular cholesterol or ceramide content. Instead, loss of ABCA12 results in defects in the genesis and fusion of insulin secretory granules and increases in the abundance of lipid rafts at the cell membrane. These changes are associated with dysregulation of the small GTPase CDC42 and with decreased actin polymerisation. Our findings establish a new, pleiotropic role for ABCA12 in regulating pancreatic lipid homeostasis and insulin secretion. Synopsis: The lipid transport protein ABCA12 plays pleiotropic roles in regulating glucose stimulated insulin secretion from beta cells, regulating the morphology and fusion of insulin granules, lipid raft abundance and the actin cytoskeleton. Beta cell specific deletion of Abca12 in mice results in progressive impairment of glucose stimulated insulin secretion, islet inflammation and beta cell death. The actions of the protein are independent of the related cholesterol transporters ABCA1 and ABCG1, which themselves regulate insulin secretion. Loss of ABCA12 results in abnormal insulin granule morphology and fusion, dysregulation of the small GTPase CDC42 and altered actin polymerisation leading to changes in lipid rafts. Abstract : The lipid transport protein ABCA12 plays pleiotropic roles in regulating glucose stimulated insulin secretion from beta cells, regulating the morphology and fusion of insulin granules, lipid raft abundance and the actin cytoskeleton.